Exclusive breastfeeding and postpartum depression: A protective association that is not modified by feeding intentions - Rachel A. Ryan; Lauren T. Berube; Andrea L. Deierlein (PLoS ONE, 2026)
Approximately 13% of women in the United States (U.S.) experience postpartum depression (PPD), a mood disorder that negatively affects maternal and infant wellbeing. Breastfeeding may protect against PPD and breastfeeding intentions may moderate this relationship. This study examined the association between breastfeeding status and PPD symptoms and whether exclusive breastfeeding intentions moderate this relationship in low-income women in the U.S. We utilized data from the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Infant and Toddler Feeding Practices Study-2, a longitudinal cohort study of caregiver feeding practices and nutrition outcomes among children enrolled in WIC. Exclusive breastfeeding intentions were measured prenatally; breastfeeding status at 1 month; and PPD symptoms at 3 months postpartum using the Edinburgh Postpartum Depression Scale (elevated PPD symptoms defined as EPDS ≥ 10). We conducted logistic regression to examine the association between breastfeeding status and elevated PPD symptoms. We stratified the analysis by exclusive breastfeeding intention-status groups to assess moderation. Adjusted models controlled for self-reported maternal ethnicity, annual household income, and smoking during pregnancy. The analytic sample included 2,022 mothers who identified their race as Black or African American (20.7%), White (58.8%), or other (20.6%), and their ethnicity as Hispanic (48.1%) or non-Hispanic (51.9%). The majority were ≥20 years old (88.2%), not married (68.2%), and had a high school education or less (62.7%). Compared to mothers who exclusively breastfed, those who combination fed (AOR, 2.03; 95% CI, 1.23–3.40) or exclusively formula fed (AOR 2.03; 95% CI 1.16–3.42) at 1 month had higher odds of elevated PPD symptoms. Exclusive breastfeeding intentions did not moderate this relationship. While exclusive breastfeeding was associated with a lower likelihood of experiencing elevated PPD symptoms, the majority of participants did not meet their exclusive breastfeeding intentions, highlighting the need for enhanced breastfeeding support.